2021
DOI: 10.1111/jfpp.16043
|View full text |Cite
|
Sign up to set email alerts
|

Siamese network‐based computer vision approach to detect papaya seed adulteration in black peppercorns

Abstract: Food adulteration is a growing peril for consumers, traders, and manufacturers worldwide. Food fraud costs the economy a fortune and creates mistrust among consumers and merchants. Black Pepper is a valuable and heavily adulterated spice. This study explores the ability of deep learning coupled with image processing to identify black pepper contaminated with its common adulterant papaya seeds. Prevalent methods work on a relatively small sample, requiring specialization and resources. Our research proposes a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…the number of classes in the classification [18]. These interpret the result as a forecast between the categories.…”
Section: Proposed Systemmentioning
confidence: 99%
“…the number of classes in the classification [18]. These interpret the result as a forecast between the categories.…”
Section: Proposed Systemmentioning
confidence: 99%
“…For food defect detection, Patel et al ( 17 ) developed a method using monochrome cameras for automatic mango sorting, and result showed that the system’s detection efficiency and accuracy reached 97.88% and 88.75%, respectively. Noor Fatima et al ( 18 ) used industrial cameras combined with deep learning to develop a device for tracking the adulteration of papaya seeds in black pepper. Furthermore, machine vision can identify and classify food products based on their color.…”
Section: Collection Of Tested Food Informationmentioning
confidence: 99%
“…Other interesting applications include the use of E-nose for the classification of carrots in terms of surface defects (presence of bad spots, abnormalities, and formation of fibrous roots) [ 15 ] and the discrimination of cheese according to aging period [ 16 ], E-eye to detect adulteration of black peppercorns with papaya seeds [ 17 ], and E-tongue to identify adulterated wine [ 18 ]. All these studies support the emerging role of electronic tools in several lines of research related to food quality.…”
Section: Introductionmentioning
confidence: 99%